2012
DOI: 10.1021/op3001959
|View full text |Cite
|
Sign up to set email alerts
|

Where Has My Acid Gone? Understanding the Self-Catalyzed Esterification of Maleic Acid in Methanol During Salt Formation

Abstract: The kinetics of the esterification of maleic acid in methanol have been investigated following the contamination of a batch of an API maleate salt with the corresponding monomethyl maleate salt. The esterification was found to be catalyzed by H + generated by the ionization of maleic acid, giving rise to an observed rate law with a one-and-a-half-order dependence upon the maleic acid concentration. On the basis of the measured rate constants over a range of temperatures a predictive model has been developed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, the ionization of MMO can be ignored during the hydrolysis because, according to the structures of MMO and oxalic acid, the ionization capability of MMO should be much weaker than that of oxalic acid. A similar case was reported by Ashworth et al, 20 who assumed that monomethyl maleate did not catalyze the esterification of maleic acid because monomethyl maleate (pK a = 8.3 in methanol) was observed to have a considerably lower acidity than maleic acid (pK a = 5.5 in methanol).…”
Section: Resultssupporting
confidence: 80%
“…Furthermore, the ionization of MMO can be ignored during the hydrolysis because, according to the structures of MMO and oxalic acid, the ionization capability of MMO should be much weaker than that of oxalic acid. A similar case was reported by Ashworth et al, 20 who assumed that monomethyl maleate did not catalyze the esterification of maleic acid because monomethyl maleate (pK a = 8.3 in methanol) was observed to have a considerably lower acidity than maleic acid (pK a = 5.5 in methanol).…”
Section: Resultssupporting
confidence: 80%
“…Kinetic experiments were run using this system and the findings were published, as it was found that the reaction forming the mono-product was self-catalytic. 46 In this case, the reaction was found to be catalytic with an order of 0.5, meaning that the overall order with respect to the maleic acid was 1.5 in forming the mono-product. The consecutive reaction forming the di-product is also catalytic with respect to the maleic acid with a 0.5 order dependence.…”
Section: Resultsmentioning
confidence: 83%
“…According to the widely recognized acid‐catalyzed hydrolysis mechanism 20, the mechanistic steps of MG hydrolysis are supposed to involve: the protonation of MG with a hydrogen ion, the attack of water on the protonated MG, proton transfer, and the elimination of methanol and protons. The attack of water on the protonated ester is the rate‐determining step 15, 16, 19, 21, whereas the other steps quickly approach equilibrium. Then, the mechanism of MG hydrolysis can be simply denoted as reactions (2) and (3).…”
Section: Resultsmentioning
confidence: 99%